Children's preferences for TV show hosts: an international perspective on learning from television. Issue 4 (1st October 2016) - Holler, Andrea; Götz, Maya; Alper, Meryl
Abstract: The human hosts of knowledge-focused TV programs for children play a significant role in young people's discoveries about themselves and the world. The fact that the majority of these personalities are slim, young, and White men, and the unquestioned truism among TV producers that children prefer such hosts, led an international research team to ask 3399 youth ages 7–10 from 27 countries to describe their ideal host, as well as themselves, through linguistically sensitive and age-appropriate surveys. Key findings include that the same percentage of boys and girls (84%) prefer hosts of the same gender, and that children self-identifying as having non-"light" skin tones are far less likely than those with a "light" skin tone to prefer hosts of the same skin color. These results suggest that marginalized children worldwide struggle to see themselves represented through respected TV figures, which has broader implications for their identity development and socialization.